Observation of four-fold azimuthal angle dependence in the terahertz radiation power of (100) p-InAs - Estacio, Elmer (Animo Repository, 2006)
The azimuthal angle dependence of the terahertz (THz) radiation power of (100) p-type InAs under 1-T magnetic field is presented. Results exhibited four-fold symmetry for the s-polarized THz radiation power. Moreover, the two-fold symmetry for the p-polarized THz radiation was modified to four-fold symmetry for a 1-T applied magnetic field. A tentative explanation regarding a magnetic field-enhanced L-valley carrier scattering is proposed. The actual physical origin of these results is currently under investigation. ©2006 IEEE.